2005
DOI: 10.1097/00004650-200503000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing a Patientʼs Spiritual Needs

Abstract: Seven major constructs-belonging, meaning, hope, the sacred, morality, beauty, and acceptance of dying-were revealed in an analysis of the literature pertaining to patient spiritual needs. The authors embedded these constructs within a 29-item survey designed to be inclusive of traditional religion, as well as non-institutional-based spirituality. This article describes the development of a multidimensional instrument designed to assess a patient's spiritual needs. This framework for understanding a patient's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 46 publications
4
77
0
9
Order By: Relevance
“…One of the differences in this scale with existing tools (22)(23)(24) was the emphasis of the designed scale on the religious dimension so that 9 phrases related to this dimension have had the highest load factor among phrases compared with other dimensions. Spirituality is thought and belief broader than religion, though in many people, this concept is declared and evolved through religious rituals, such as prayer (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the differences in this scale with existing tools (22)(23)(24) was the emphasis of the designed scale on the religious dimension so that 9 phrases related to this dimension have had the highest load factor among phrases compared with other dimensions. Spirituality is thought and belief broader than religion, though in many people, this concept is declared and evolved through religious rituals, such as prayer (35).…”
Section: Discussionmentioning
confidence: 99%
“…The response to this need requires its measurement (20). There are, now, 4 tools for evaluating spiritual needs in the world, which include questionnaires on spiritual need; Bussing et al (24), which were designed based on the culture prevailing in their respective countries.…”
Section: Introductionmentioning
confidence: 99%
“…In German patients with chronic pain diseases and cancer, factor analysis differentiated four main dimensions [25], i.e., religious needs (enrolling praying, participate at religious ceremony, reading religious/spiritual books, turning to a higher presence), need for inner peace (enrolling patients' wishes to dwell at places of quietness and peace, beauty of nature, finding inner peace, talking with other about fears and worries, devotion by others), existential needs (in terms of reflection and meaning in life and suffering, dissolve open aspects in life, talk about the possibility of a life after death), and actively giving (which addresses the active and autonomous intention to solace someone, to give away something from yourself, and turning to others). Galek's analysis of the literature revealed seven major constructs, i.e., love and belonging, meaning and purpose, hope and peace, the sacred, appreciation of beauty, morality and ethics, resolution and death [26]. A meta-summary of the qualitative literature on spiritual perspectives of adults extracted thematic pattern of spirituality at the end of life, which were spiritual despair (alienation, loss of self, dissonance), spiritual work (forgiveness, self-exploration, search for balance), and spiritual well-being (connection, self-actualization, consonance) [27].…”
Section: Needs Of Patients With Chronic Diseasesmentioning
confidence: 99%
“…: Rel(igious), Mean(ing), Peace, Con(nection). In a study among chaplains from the United States of America and Canada, Flannelly et al [30] used the Spiritual Needs Assessment scale (developed by Galek et al [26] after analysis of the literature to assess patients' spiritual needs) to assess the number of times that chaplains encounter patients with various spiritual needs. They found that Meaning and Purpose, Love and Belonging, and Hope, Peace and Gratitude ranked the highest, and Morality/Ethics and Appreciation of Art and Beauty the lowest, while the dimensions Religion and Divine Guidance and Death Concerns and Resolutions, which could be regarded as the central tasks of chaplains, are ranked between [30].…”
Section: Figure 2 Spiritual Needs Of Patients With Chronic Diseases mentioning
confidence: 99%
“…One response to this challenge was the develeopment of scales to assess the degree to which hospital patients are satisfied with pastoral care (VandeCreek, 2004) and the degree to which chaplains have met their spiritual and emotional needs (Flannelly, Oettinger, Galek, Braun-Storck, & Kreger, 2009). Related approaches have developed scales to measure patients spiritual needs and the effectiveness of chaplain interventions (Flannelly, Galek, & Flannelly, 2006;Flannelly, Galek, Tannenbaum, & Handzo, 2007;Galek, Flannelly, Vane, & Galek, 2005).…”
mentioning
confidence: 99%